Randomised, placebo-controlled, double-blinded trial of fecal microbiota transplantation in severe obesity: a study protocol - Hanssen, Hege Marie; Fjellstad, Maria Serafia; Skjevling, Linn; Johnsen, Peter Holger; Goll, Rasmus; Almå, Kristin Helen; Kulseng, Bård Eirik; Valle, Per Christian (BMJ Open, 2023)
Introduction - Obesity is one of the main threats to public health in western countries and increases the risk of several diseases, overall morbidity and mortality. Sustained weight loss will reduce risk factors and improve several obesity comorbidities. Options are conservative treatment such as lifestyle changes, bariatric surgery or medications. Conservative treatment has a low success rate, and bariatric surgery is typically not reversible, with the risk of complications and recurrences. Treatment of obesity with medications has in recent years shown great promise, but the side effects are many, and the long-term effect is unknown. There is also a need for an option for patients where surgery has contraindications and conservative follow-up does not succeed. The research on obesity and gut microbiota has yielded promising results regarding weight reduction and metabolic health, but more research is needed to better understand the relationship between gut microbiota and severe obesity. This study could show proof of concept that gut microbiota from a lean donor could, in addition to lifestyle intervention, contribute to weight reduction in people suffering from severe obesity. Method and analysis - This study aims to investigate if a fecal microbiota transplantation (FMT) from a lean donor leads to weight reduction in participants suffering from severe obesity. The study is a single-centre, double-blinded, placebo-controlled, parallel-group study with 60 participants. Participants will be randomised 1:1 for FMT from a lean donor or placebo. FMT or placebo will be delivered once by enema. We will include participants from the outpatient clinic for severe obesity, at the Medical Department, University Hospital of North Norway, Harstad, by invitation only. The study has a follow-up period of 12 months, with study visits of 3, 6 and 12 months post FMT. The primary endpoint is a weight reduction of ≥10%, 12 months after intervention. The results of the study will be published in open access journals. At the end of ...